Draft Annual Plan 1994-95 Volume-I Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1994)
The Andaman and Nicobar archipelago comprises 572 Islands (including 265 rocks and islets) with a total geographical area of 8249 Sq. Kms. the Andaman group stretches from 9°N to 14°N, over 464 kms. in length and with a maximum width of 51 kms. the Nicobar Group comprising Car Nicobar, Nancowry Group of Islands and Great Nicobar Islands are scattered over 293 kms, between 9 to 6 North of the equator. The Islands have an irregular land surface with steep hills and valleys, covered almost entirely by a rich and tropical forest cover that holds down a friable top soil against steep run off from a heavy rainfall of 3180 millimeters (average) received during 8 months of the year.
Andaman and Nicobar Administration